From model rooms towards a modelled indoor environment. (1st October 2016) - Stratev, D.; Fürhapper, C.; Niedermayer, S.; Habla, E.; Nohava, M.; Weigl, M.
Abstract : This paper is divided into two parts: In the first part, the model room VOC measurement concept is evaluated with specimens from different construction materials in order to estimate the safety margins when using day 28 as the time point for indoor air quality assessment. Safety margins between 2 and 20 were estimated for softwood-based products. In the second part, the theoretical restrictiveness of ECA-IAQ Report 18 derivative schemes (like AgBB or NH 105) towards the indoor-related industrial production in central Europe was evaluated.